Interventions for drug users in the criminal justice system: Scottish review - Malloch, Margaret S. (Report, 2011)
The purpose of this review was to examine the available research evidence on criminal justice interventions in Scotland in terms of “effectiveness”, (measured by rates of reconviction/reoffending, and reductions in drug use) and costs. The review also recognises the current policy emphasis on “recovery”, which requires a wider acknowledgement of the possible mechanisms for measuring “success” and a wider vision for the process of recovery itself. The review was undertaken between August and November 2010.